Pemberdayaan Warga melalui Edukasi Pembuatan Eco-Enzyme dan Strategi Pemasaran Produk Turunan Eco-Enzyme di Kawasan RT. 48 Kelurahan Sepinggan, Balikpapan - Rosmiati Rosmiati; Khairil Anam; Yusnita Manalu (Jurnal Pengabdian Masyarakat, 2026)
The problem of organic waste processing in dense residential areas such as RT.48 Sepinggan Village, Balikpapan, has become an issue in environmental sustainability. RT residents. 48 Sepinggan Villages are quite active in reforestation competition activities. However, the lack of active participation in organic waste processing, especially household organic waste, is an obstacle. To answer this challenge, community empowerment activities are carried out based on training and education in processing household waste into multipurpose products, namely eco-enzymes, which are fermented liquids of organic waste with various environmental benefits. This program not only focuses on knowledge and technical skills in the manufacture of eco- enzymes, but also increases ecological awareness, and opens up opportunities for the development of micro-businesses through the management of eco-enzymes into various products with selling value. All of this supports economic and environmental sustainability efforts in the city of Balikpapan. Through a systematic approach to training, mentoring, and monitoring, this activity was able to increase residents' understanding of the importance of waste sorting, the use of organic waste, and strengthening the values of mutual cooperation.